2012
DOI: 10.1103/physrevlett.109.137004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Superconductivity by Twin Boundaries in FeSe

Abstract: Low-temperature scanning tunneling microscopy and spectroscopy are employed to investigate twin boundaries in stoichiometric FeSe films grown by molecular beam epitaxy. Twin boundaries can be unambiguously identified by imaging the 90• change in the orientation of local electronic dimers from Fe site impurities on either side. Twin boundaries run at approximately 45• to the Fe-Fe bond directions, and noticeably suppress the superconducting gap, in contrast with the recent experimental and theoretical findings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 32 publications
11
125
0
1
Order By: Relevance
“…In Sn, ξ ∼ 240 nm is considerably larger than the size of the studied nanoparticles, 33 from which ∆ should change little with positions in a specific particle. However, ξ was found to be only 5.5 nm in thick FeSe films 34 and even smaller for single UC FeSe films due to the dimensionality effect. This appears smaller than the average lateral nanoflake size A 0.5 in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In Sn, ξ ∼ 240 nm is considerably larger than the size of the studied nanoparticles, 33 from which ∆ should change little with positions in a specific particle. However, ξ was found to be only 5.5 nm in thick FeSe films 34 and even smaller for single UC FeSe films due to the dimensionality effect. This appears smaller than the average lateral nanoflake size A 0.5 in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In-situ scanning tunneling spectroscopy (STS) on MBE grown FeSe thin films was interpreted as evidence for gap nodes by Song et al [13]. These authors observed one very clear single Vshaped energy gap with ∆ B ≈ 2.2 meV [13][14][15][16], which corresponds to ratios of 2∆ B /k B T c = 5.5 − 6.4. An additional conductivity feature at 2∆ C ≈ 9.4k B T c , was interpreted as strong coupling to a spin fluctuation mode [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Fe site defect is surrounded by a larger electronic dimer structure: a C 2v -symmetric depression in dI/dV oriented along the Fe-Fe direction (100 pA, 10 mV). 50 (b) Average dI/dV centered at a Co substitution at a Fe site in Ca(Fe 1Àx Co x ) 2 As 2 showing a similar large electronic dimer structure. 76 (c) Topograph of an impurity in nominally stoichiometric LiFeAs showing the smaller dumbbell shape, but lacking the larger electronic dimer (10 pA, 20 mV).…”
Section: Single Atom Defects As Local Probesmentioning
confidence: 99%
“…6a). 45,50 The smaller dumbbellshaped signature is present in topographs taken up to 3.5 V imaging bias, but the larger, B16a Fe-Fe sized dimers only appear at around AE20 mV bias, pointing towards their electronic origin. Furthermore, the larger features are always oriented along the orthorhombic a (longer, antiferromagnetic) Fe-Fe axis, as they change their orientation by 901 across an orthorhombic twin boundary, regardless of the stochastic orientation of the smaller dumbbell-shaped signature.…”
Section: Single Atom Defects As Local Probesmentioning
confidence: 99%